PROBLEMS OF PRESERVING NATIONAL IDENTITY IN CROSS-BORDER MIGRATION PROCESSES - Mirzayev Buniyot Shokirjonovich (Next Scientists Conferences, 2025)
Cross-border migration presents significant challenges to the preservation of national identity in both origin and destination countries. This article examines the multifaceted problems that arise when migration processes threaten established conceptions of national belonging, cultural continuity, and collective identity. Through analysis of demographic pressures, cultural dilution concerns, generational disconnection, and institutional challenges, this study reveals how migration can undermine traditional mechanisms of national identity preservation. The article explores both the legitimate concerns about cultural continuity and the adaptive strategies societies employ to maintain coherent national identities while accommodating demographic change.